2019
DOI: 10.1038/s41598-019-48028-0
|View full text |Cite
|
Sign up to set email alerts
|

Geometric principles of second messenger dynamics in dendritic spines

Abstract: Dendritic spines are small, bulbous protrusions along dendrites in neurons and play a critical role in synaptic transmission. Dendritic spines come in a variety of shapes that depend on their developmental state. Additionally, roughly 14–19% of mature spines have a specialized endoplasmic reticulum called the spine apparatus. How does the shape of a postsynaptic spine and its internal organization affect the spatio-temporal dynamics of short timescale signaling? Answers to this question are central to our unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 81 publications
(78 reference statements)
1
56
0
Order By: Relevance
“…Intracellular pattern formation in general is based on cycling of proteins between cytosolic and membrane/cortex-bound states; see for example the Cdc42 system in budding yeast and fission yeast (33,58), the PAR system (46,59) in C. elegans, excitable RhoA pulses in C. elegans (60), Xenopus and starfish oocytes (61), and MARCKS dynamics in many cell types (62,63). Further examples include, intracellular signaling cascades (64)(65)(66)(67) and, potentially, intercellular signaling in tissues and biofilms. Our study shows that it is essential to explicitly take the bulk-surface coupling into account when one investigates such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pattern formation in general is based on cycling of proteins between cytosolic and membrane/cortex-bound states; see for example the Cdc42 system in budding yeast and fission yeast (33,58), the PAR system (46,59) in C. elegans, excitable RhoA pulses in C. elegans (60), Xenopus and starfish oocytes (61), and MARCKS dynamics in many cell types (62,63). Further examples include, intracellular signaling cascades (64)(65)(66)(67) and, potentially, intercellular signaling in tissues and biofilms. Our study shows that it is essential to explicitly take the bulk-surface coupling into account when one investigates such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that the coupled dynamics of signaling and actin remodeling can alter spine volume in a biophysical model [67] without considering the geometry of the spines or considering the role of spine shape in regulating different signaling pathways [114][115][116][117][118]. In this work, we present a simplified mechanical model for studying the role of different force distributions and energy contributions that are associated with the different spine shapes noted in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…For example, fluorescence experiments have shown that the dendritic spine necks act as a diffusion barrier to calcium ions, preventing ions from entering the dendritic shaft [112]. Complementary to this and other experiments, various physical models solving reaction-diffusion equations in idealized geometries have been developed to further interrogate the structure-function relationships [51,100,111,[117][118][119].…”
Section: Discussionmentioning
confidence: 99%